REFRAMING THE MAIN CHARACTERS USING NLP TECHNIQUES IN PETE DOCTER’S MOVIE “SOUL (2020)” - Angelina Br Simanungkalit,; Rita Hartati,; Rita Hartati, (Jurnal Cakrawala Ilmiah, 2025)
Reframing is a language strategy in neuro linguistic programming (NLP) that changes an individual’s perception by altering the meaning or context of an experience. This study uses Richard Bandler and John Grinder’s (1982) theory of reframing to analyze reframing techniques in Pete Docter’s Soul (2020), supported by language attributes such as modality, lexical, temporal and Pragmatic shift. Language attributes can serve as indicators that reveal how language structure affects a character’s thoughts, feelings, and transformations. This study used a qualitative descriptive approach, examining dialogue and narrative elements to identify reframing expressions and their language patterns. A total of 50 data points were found: 27 positive reframings (54%), 17 neutral reframings (34%), 3 temporal reframings (6%), and 3 situational reframings (6%). The results of the study showed that positive reframing was the most prominent, highlighting its impact on character development and shifts in thought patterns. The process of reconstruction, especially in characters such as Joe Gardner and 22, embodies a deeper understanding of the meaning of life and personal identity, which is constructed through the conscious use of language. This can be very helpful in vulnerable or stressful situation, leading to good communication and how to deal with difficult circumstances.It is hoped that the result is useful for everyone who wants to study about NLP Reframing techniques.